Konsep Waliyu Al-Amri Al-Daruri Bisysyaukah sebagai Legalitas Keabsahan Pemilihan Umum di Indonesia - Afif Hidayatul Mahmudah; Faisol Mubarok; Faiqatul Himmah (Rechtenstudent, 2021)
This research aims to examine the concept of waliyu al-amri al-daruri bisyaukah whether in determining the legality of election results in Indonesia. The research method used is normative law with an approach to Islamic law and positive law regarding elections. This is necessary to study because in the General Election process (Election) in Indonesia there is a fraud, so the concept of waliyu al-amri al-daruri bisyaukah can be present as a rule of reference for legality. the validity of the election results. Procedurally, it should be passed through lawful ways in obtaining legitimate leadership and not violating norms in society. Based on the research results, Mahfud MD, the former Chief Justice of the Constitutional Court, stated that there is always fraud in the election and cannot be avoided. The existence of this concept does not necessarily apply as stipulated in Islamic law to get a leader, because it is impossible to apply. Indonesia is not an Islamic country, but a country that stands on the basis of agreement or democracy. Indonesia is a state of law, the provisions that apply in society have been accommodated in the law and the presence of the Constitutional Court as an arbitrator in resolving election dispute problems. Based on the concept of waliyu al-amri al-daruri bisyaukah, can the election results even be carried out with an element of fraud and have been approved by the Constitutional Court, they will remain valid in the eyes of the law, both positive law and Islamic law.